Layanan Pengolahan Air Limbah Binatu bagi Usaha Mikro, Kecil, dan Menengah dengan Teknik Filter Karbon Aktif - Togibasa, Octolia; Dahlan, Khaeriah; Silalahi, Rivaldo Titto Ulrich; Sikwa , Afrianus (Bakti Hayati: Jurnal Pengabdian Indonesia, 2023)
Laundry activities utilizing detergents as cleaning agents generate non-degradable waste, posing environmental and health hazards. Laundry services, or laundries, have experienced rapid growth in Jayapura City, resulting in substantial laundry waste discharge directly into the environment. Activated carbon, with its porous and highly absorptive nature, proves effective to absorb waste particles. This community engagement initiative focuses on providing education and implementing small to medium-scale laundry waste treatment for micro, small, and medium-sized enterprises. The project collaborates with Zifara Laundry, a laundry business located in Waena, Heram District, Jayapura City. The partner receives essential education on the importance of pre-treating laundry waste before disposal into the environment. The engagement team installs waste filters based on activated carbon, augmented with silica sand, gravel, and cotton filters in each layer. As a result, both the business owner and laundry workers gain a profound understanding of the significance of treating laundry waste before environmental discharge. The waste filters installed by the engagement team on the central laundry waste disposal channel contribute to an improvement in laundry wastewater quality. Turbidity levels decrease from a scale of 150-200 NTU to 1-2 NTU after the installation of activated carbon-based laundry waste filters.